The Viennese café and fin-de-siècle culture - Ashby, Charlotte, 1979-; Gronberg, Tag; Shaw-Miller, Simon, 1960- (Austrian and Habsburg studies, 2013)
The Viennese café was a key site of urban modernity around 1900. In the rapidly growing city it functioned simultaneously as home and workplace, affording opportunities for both leisure and intellectual exchange. This volume explores the nature and function of the coffeehouse in the social, cultural and political world of fin-de-siècle Vienna. Just as the café served as a creative meeting place within the city, so this volume initiates conversations between different disciplines focusing on Vienna 1900. Contributions are drawn from the fields of social and cultural history, literary studies.